World genera of Mastigitae: review of morphological structures and new ecological data (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
Mastigitae comprise most unusual ant-like stone beetles, showing intriguing morphological characters and ecological adaptations. The largest adults among Scydmaeninae can be found in this group; some reaching nearly 9 mm in length, but there are also adults as small as 1.10 mm. Members of Leptomastacini are microphthalmous and depigmented; Mastigini are often black or contrastingly bicolored and have diurnal life style, adults of some species climbing bushes and trees. Papusini inhabit the driest North American deserts and are active during the warmest time of the year; other taxa live in subtropical forests; some are known to enter caves. Adults of some genera have enigmatic modifications of maxillary palps, postgenae or antennae, whose functions still remain unknown. In one genus the male genitalia are enormously elongate, so that these beetles have evolved a method of copulation not known in any other Coleoptera. The evolutionary history of Mastigitae is documented by fossils since the Upper Cretaceous, and extinct forms are even more ’extreme’ in their spiny antennae and unusually elongate appendages than their extant relatives. Although phylogenetic hypotheses have been proposed to clarify the relationships and classification of Mastigitae, morphological structures of most genera remain undescribed. They are reviewed in the present synopsis, with detailed descriptions and illustrations of adult structures of all extant genera (Ablepton, Leptomastax, Taurablepton, Mastigus, Palaeostigus, Stenomastigus, Leptochromus, Clidicus and Papusus), with a brief review of known larval forms and fossils. Novel ecological data are given, with emphasis on habitat preferences and feeding behavior. The ’springtail trap’ hypothesis for the spiny antennae of Mastigini is rejected, based on field observations and laboratory experiments. For the first time, details of feeding for Palaeostigus and Leptomastax are described. A checklist of species is given, and the main problems related to the classification, phylogeny and ecology of Mastigitae are discussed.